A Colour Scheme Authenticated Tutor Booking Website - A. O., Oke; L. I., Ogbewey; J. P., Oguntoye; A. A., Jubril; E. S., Shokenu (Engineering And Technology Journal, 2023)
Authentication is the first and most important step in information security. Traditional password authentication systems are not strong enough to cope with the current age of cybercrime because passwords can be easily predicted by attackers. This paper aims at reducing threats from different malicious activities to a great extent, thereby increasing security and efficiency, proving it to be very advantageous in today’s world where confidential data security has become so essential. This system provides users with the freedom to have complete security while handling their confidential data and security essential systems from anywhere. The colour code authentication scheme is executed using colour features for passwords, where users have to select a colour code as password item in terms of the uniqueness and reliability with which it can be entered. This technique uses a grid for session passwords generation and is resistant to dictionary attacks, brute force attacks, and shoulder-surfing. The colour scheme allocated ratings to colours, based on these ratings and the grid displayed during login, session passwords were generated. This work explored a new and easy password authentication system devoid of memorization and recall. This authentication system makes data more secure as only the colour rating at the registration phase needs to be remembered. The Colour based authentication system would provide an efficient way to encrypt account details for sensitive applications such as defense and banking.